The Importance of Urban Planning and Landscape Design in the Process of Creating ‘Great Places’ for Citizens - Case study of Park Macedonia 1 - Brndevska Stipanović, Viktorija; Čukanović, Jelena; Andonovski, Vlatko; Minchev, Ivan; Orlović, Saša (SEEFOR, 2025)
Creating places where urban life is better and of a higher quality is one of the main tasks of the modern society. These places are called ‘great places’ and urban parks have all the predispositions to be one of them. Due to the functions they perform, they are a necessary part of every city. Urban planning and landscape design are very important in the process of creating ‘great places’ for citizens. With their proper use, successful green spaces are created, which are functional and aesthetic at the same time. This is especially important since green areas in the urban environment are becoming less numerous. The subject of analysis in this paper is urban planning and landscape design through the example of Park Macedonia 1 in Skopje, North Macedonia. The park is analysed from different aspects (functionality, safety, plant species selection, layout of the plants and the use of basic principles of landscape design) to determine if this place is a ‘great place’, i.e. whether this place at the same time functional and aesthetic. The results show that Park Macedonia 1 is a ‘great place’; however, there are some gaps in its urban planning and landscape design. These gaps are reflected in the safety of the visitors and the functionality of the park, made in the process of plant species selection and landscape designing of the park, i.e. entrances and exits, layout of plants, incorrect use of focal points, and simplicity, rhythm and line as basic principles of landscape design. Analyses of Park Macedonia 1 in terms of urban planning and landscape design and the proposals for corrections can be used in the future design of ‘great places’ in urban areas like Skopje.
Keywords: landscape architecture; Park Macedonia; successful places; urban forestry; urban greenery; urban parks